DETERMINING THE MENTAL STATE OF THE ATHLETE USING PSYCHOLOGICAL (American Journal of Interdisciplinary Research and Development, 2022)
The article describes methods for determining the mental state of athletes using diagnostics based on express-adequate psychological methods.